2013
DOI: 10.3917/grh.133.0093
|View full text |Cite
|
Sign up to set email alerts
|

The impact of work overload and coping mechanisms on different dimensions of stress among university teachers

Abstract: Le métier d’enseignant universitaire n’est plus considéré comme une profession peu stressante comme il l’a été souvent jusqu’à présent [Winelfield et al., 2003] dans les pays occidentaux, mais aussi dans des pays en voie de développement comme le Pakistan où cette étude a été réalisée. Au Pakistan, le secteur de l’enseignement supérieur s’est fortement développé depuis l’année 2000 et la concurrence s’est accrue du fait de l’arrivée de plusieurs universités privées, avec pour conséquences de lourdes responsabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…These include work overload (Thorsen, 1996;Abbas & Roger, 2013;Gupta, Rao, & Mukherjee, 2015), work-life imbalance, (Slišković & Maslić Seršić, 2011;Kinman & Jones, 2008;Rafeeq & Harish, 2015), decreased job satisfaction (Brewer & McMahan-Landers, 2013;Reevy & Deason, 2014;Chung, 2011), increased number of students to teach (Easthope C. & Easthope G., 2000;Jamison & Enrera, 2015;Gartia & Sharma, 2013), lack of university funding, resources and recognition (Gillespie, Walsh, Winefield, Dua, & Stough, 2001;Reevy & Deason, 2014;Gupta et al, 2015) and lack of administrative and colleague support (Slišković & Maslić Seršić, 2011;Kavitha, Religious coping, one of the most common coping strategies, is defined as the use of religious beliefs and practices in the facilitation of problem solving in order to easily adapt and to prevent or alleviate the negative emotional effects of the stressful situation (Pargament, Smith, Koenig, & Perez, 1998). The use of religion was shown to help Filipino workers such as fast-food chain workers (Ereno et al, 2014) and policemen (Inasoria, 2014) in decreasing their work stress and in improving their job performance.…”
Section: Factors Of Faculty Stressmentioning
confidence: 99%
“…These include work overload (Thorsen, 1996;Abbas & Roger, 2013;Gupta, Rao, & Mukherjee, 2015), work-life imbalance, (Slišković & Maslić Seršić, 2011;Kinman & Jones, 2008;Rafeeq & Harish, 2015), decreased job satisfaction (Brewer & McMahan-Landers, 2013;Reevy & Deason, 2014;Chung, 2011), increased number of students to teach (Easthope C. & Easthope G., 2000;Jamison & Enrera, 2015;Gartia & Sharma, 2013), lack of university funding, resources and recognition (Gillespie, Walsh, Winefield, Dua, & Stough, 2001;Reevy & Deason, 2014;Gupta et al, 2015) and lack of administrative and colleague support (Slišković & Maslić Seršić, 2011;Kavitha, Religious coping, one of the most common coping strategies, is defined as the use of religious beliefs and practices in the facilitation of problem solving in order to easily adapt and to prevent or alleviate the negative emotional effects of the stressful situation (Pargament, Smith, Koenig, & Perez, 1998). The use of religion was shown to help Filipino workers such as fast-food chain workers (Ereno et al, 2014) and policemen (Inasoria, 2014) in decreasing their work stress and in improving their job performance.…”
Section: Factors Of Faculty Stressmentioning
confidence: 99%
“…In the era of globalization and the advancement of technologies, the work environment has become more competitive and demanding, with work overload and stress imposed on workers, and academics are no exception. The disparities between the enduring and demanding work requirements and the capacity of academicians to tackle these demands ultimately culminate in burnout and emotional distress (1). Professional burnout is a psychological state that negatively impacts one's relationship with one's work, resulting in emotional exhaustion, reduced job engagement, commitment, and inappropriate practice within the work environment (2).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research examined the relationship between coping styles and burnout among healthcare professionals and found that task-oriented and adaptive coping was associated with a decreased risk of burnout, potentially improving staff well-being (9,10). Moreover, individual-level coping capacities and handling workplace dynamics have also been found to shape the risk of stress and burnout and affect mental well-being among academic individuals (1,11). Several recent reports have highlighted the ongoing risk of burnout in academia, resulting in a quiet quitting phenomenon in some cases that might affect the long-term sustainability of high-quality education (12).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research explored occupational stressors and coping strategies amongst academics in other countries (Abbas & Roger, 2013;Ablanedo-Rosas, Blevins, Gao, Teng, & White, 2011;Broadbent, 2013;Darabi et al, 2017;Holton, Barry, & Chaney, 2016;Johnson, Willis, & Evans, 2018;Poalses & Bezuidenhout, 2018), but researchers have devoted little attention to producing a more holistic view of coping with occupational stress in a South African higher education context. Researchers have also become increasingly interested in emotional experiences during stressful life events (such as chronic illnesses), but have devoted little attention to the emotions that employees experience when confronted with occupational stressors.…”
Section: Introduction Background To and Rationale For The Studymentioning
confidence: 99%